Effects of glycerol on “in vitro”-grown “Amaranthus retroflexus” L. - BANCIU, Cristian; MANOLE, Anca; MARIA, Gabriel-Mihai (Studia Universitatis Babeș-Bolyai Biologia, 2016)
Our experiments used a robust plant species (Amaranthus retroflexus), that grows on various types of substrate and in a variety of stress conditions (drought, frost, flooding, etc.) to test its survival on culture media with glycerol as a substitute of sucrose. After aseptic seed germination, plantlets were grown on a calus induction culture medium (Gamborg basal medium enriched with NAA and kinetin). The non-morphogenetic calus was cultured on four culture media with ascending glycerol concentration replacing sucrose as a carbon source. The survival and the growing rate of the caluses are factors that lead to the conclusion of succesful degradation of glycerol by A. retroflexus. Further biochemical analyses will reveal the biodegradation pathways and the secondary compounds production.